STAGFLATION – PROOF BANKING: HOW FINTECH DEVELOPMENT AND FINANCIAL RESILIENCE DRIVE PROFITABILITY – ARDL MODELING EVIDENCE FROM INDONESIA'S COMMERCIAL BANKS - Prawira, Anggun Wida; Mujanah, Siti; Alif Fianto, Achmad Yanu (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study analyzes the impact of the triple-layer effect stagflation (inflation, GDP), fintech lending, and bank stability (CAR, LDR) on Indonesian banks' ROA, assessing short- and long-term effects. The object of this research is the audited financial report of Indonesian Commercial Bank KBMI IV which is listed on the Indonesia Stock Exchange. Data were collected using purposive sampling (time series of 2019-2024 period). The Autoregressive Distributed Lag (ARDL) model was applied to analyze both short-term dynamics and long-term equilibrium between the variables. The results show that: Inflation has a significant negative impact on ROA in both the short and long term. GDP does not significantly affect ROA. Fintech lending does not have a significant impact on ROA, though it may indirectly pressure banks to innovate. CAR has a significant positive influence on ROA, indicating financial resilience supports profitability. LDR does not significantly affect ROA, suggesting lending activities may not be optimal or are affected by external risks. A long-term cointegration exists between all variables and ROA, indicating the importance of strategic, forward-looking policies. The findings imply that stagflation poses a serious risk to banking profitability. Banks must strengthen risk management, improve capital efficiency, and embrace innovation to remain competitive. Policymakers should support financial stability through appropriate macroeconomic policies, especially in stagflationary conditions.